Strategi Komunikasi Persuasif Bidan dalam Meningkatkan Kepatuhan ANC (Antenatal Care) pada Ibu di Wilayah Rural - Aditia Silvia Fazila; Indra fara Nisa; Laode Aharuddin Kapege (CV. ITTC INDONESIA, 2025)
Antenatal care (ANC) services play a vital role in reducing maternal and infant morbidity and mortality rates. However, the compliance level of pregnant women with ANC visits in rural areas remains low due to social, cultural, and infrastructural constraints. This study aims to analyze the persuasive communication strategies employed by midwives to enhance ANC compliance, describe the communication interaction process between midwives and pregnant women, and identify the supporting and inhibiting factors affecting the effectiveness of persuasive communication in rural communities. The study used a qualitative approach with a case study design, involving six key informants (midwives, pregnant women, and community leaders) and two triangulation informants (health officers and community health volunteers). Data were collected through in-depth interviews, participant observations, and focus group discussions (FGDs), then analyzed inductively using source triangulation for validity. The findings reveal that effective persuasive communication strategies include empathetic, educational, and socio-community approaches, which are adapted to local cultural values and interpersonal dynamics. The effectiveness of persuasive communication is influenced by midwives’ empathy, community support, and structural conditions of health services. In conclusion, empathy-based and culturally sensitive persuasive communication enhances awareness and strengthens pregnant women’s compliance with regular ANC visits in rural areas.